Multicultural Education as a Means of Creating Harmonization in the Midst of Cultural Diversity in Indonesia - Dewi, Ni Komang Candra; Utami, A. A. Istri Dewi Adhi; Suastika, I Nengah; Anantasya, Yohana Agnes Dewi; Yanti, Putu Risma; Emben, Ni Komang Ayu Sari; Sari, Komang Ayu Dina; Putri, Raincia Salsabela (Universitas Pendidikan Ganesha, 2025)
Indonesia is a country that has a variety of diversity in it, be it diversity of religion, ethnicity, language, and culture. This diversity has the potential to create various conflicts in society. For this reason, Multicultural Education is important as a means of creating a harmonious situation in the midst of diversity in Indonesia. The purpose of this article is so that people can form awareness and understanding within themselves, to be able to respect, appreciate and be tolerant of cultural diversity in Indonesia. The method used in this research is a qualitative research method in the form of literature study by collecting relevant data, which supports the writing of this article. The result of this research is that Multicultural Education provides an understanding that cultural diversity is not an obstacle, but can be a factor that can form unity in society, so as to create a harmonious life.